Through the looking glass: Distinguishing neural correlates of relational and non-relational self-reference and person representation. (September 2020) - Long, Elizabeth U.; Wheeler, Nathan E.; Cunningham, William A.
Abstract: Background: Neuroimaging studies have found a substantial overlap between self-related and social cognitive processes. This study examines three different ways of conceptualizing a person - one that requires considering how they are embedded in their social environment (roles), one that requires considering their generalized qualities (traits), and one that identifies their relevant group memberships. To the extent that relational aspects of identity require considering how a person is embedded in their social environment we should find greater activation for role judgements in regions associated with social cognitive processes. Methods: During fMRI scanning, 38 participants made stimulus judgments about themselves and a close other regarding the target's traits, social roles, and group memberships in a 2 (target of judgment) x 3 (stimulus category) within-participant design. Results: Relatively greater activation in areas broadly associated with theory of mind and mentalizing (e.g., PCC, TPJ) was found for social role, compared to trait judgments. By contrast, trait judgments, compared to role judgments, activated regions associated with semantic memory (e.g., IFG). Conjunction analyses showed that activations associated with roles overlapped with regions associated with a meta-analytic map of mentalization, judgments made about others, and stimuli reflecting higher social specialization, indicating that roles may require considering how a person is socially embedded. Judgments about group memberships were associated with brain regions found for both trait and role judgments. Conclusion: Our findings provide evidence for a distinction between two modes of social reference - one that is relatively more associated with social relational processing (roles) and that is relatively more dependent on semantic memory processes (traits). Given the substantial overlap between the pattern of results for roles (relative to traits) and other (relative to self), it may be the case that at least part of our representation of ourselves and others may fundamentally require representing people as embedded in social networks.